2019
DOI: 10.4274/jcrpe.galenos.2018.2018.0213
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Random Luteinizing Hormone is an Unreliable Indicator for Pubertal Suppression in Girls Treated with Monthly Leuprolide for Idiopathic Central Precocious Puberty

Abstract: Objective:Longitudinal data regarding random luteinizing hormone (LH) concentrations in patients with idiopathic central precocious puberty (ICPP) during treatment are limited. Therefore, we sought to evaluate random LH and estradiol concentrations during monthly leuprolide injection and their associations with pubertal progression and final adult height (FAH) in girls with ICPP.Methods:Medical records of 27 girls with ICPP who had attained FAH were reviewed. Patients’ height, weight, Tanner stage, growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…One study in girls treated with a 50 mg histrelin implant suggested that continuous low-concentration LH secretion tapered off over time as basal LH concentrations decreased during the course of therapy ( 14 ). We did not observe this temporal decline in LH concentrations, similar to findings in another study using leuprorelin 3.75 mg ( 9 ). Whether the shorter half-life of leuprorelin 3.75 mg allows breakthrough gonadotropic activity at GnRHa trough concentrations towards the next injection remains speculative.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…One study in girls treated with a 50 mg histrelin implant suggested that continuous low-concentration LH secretion tapered off over time as basal LH concentrations decreased during the course of therapy ( 14 ). We did not observe this temporal decline in LH concentrations, similar to findings in another study using leuprorelin 3.75 mg ( 9 ). Whether the shorter half-life of leuprorelin 3.75 mg allows breakthrough gonadotropic activity at GnRHa trough concentrations towards the next injection remains speculative.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, elevated concentrations of LH did not indicate insufficient pituitary suppression as the girls never showed signs of breast tissue development, BA advancement or had increased growth velocity. In line with this report, Wiromrat and Panamonta ( 9 ) found that in spite of pubertal basal LH concentrations during GnRHa treatment, clinical measures such as Tanner stage, BA and decreased growth velocity indicated sufficient pituitary suppression. Other smaller studies in girls treated with a 50 mg histrelin implant have also reported elevated LH concentrations during treatment ( 14 , 15 ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations